Weak cis and trans Interactions of the Hemagglutinin with Receptors Trigger Fusion Proteins of Neuropathogenic Measles Virus Isolates - Shirogane, Yuta (J Virol, 2020)
Measles virus (MeV) is an enveloped RNA virus bearing two envelope glycoproteins, the hemagglutinin (H) and fusion (F) proteins. Upon receptor binding, the H protein triggers conformational changes of the F protein, causing membrane fusion and subsequent virus entry. MeV may persist in the brain, infecting neurons and causing fatal subacute sclerosing panencephalitis (SSPE). Since neurons do not express either of the MeV receptors, signaling lymphocytic activation molecule (SLAM; also called CD150) and nectin-4, how MeV propagates in neurons is unknown. Recent studies have shown that specific substitutions in the F protein found in MeV isolates from SSPE patients are critical for MeV neuropathogenicity by rendering the protein unstable and hyperfusogenic. Recombinant MeVs possessing the F proteins with such substitutions can spread in primary human neurons and in the brains of mice and hamsters and induce cell-cell fusion in cells lacking SLAM and nectin-4. Here, we show that receptor-blind mutant H proteins that have decreased binding affinities to receptors can support membrane fusion mediated by hyperfusogenic mutant F proteins, but not the wild-type F protein, in cells expressing the corresponding receptors. The results suggest that weak interactions of the H protein with certain molecules (putative neuron receptors) trigger hyperfusogenic F proteins in SSPE patients. Notably, where cell-cell contacts are ensured, the weak cis interaction of the H protein with SLAM on the same cell surface also could trigger hyperfusogenic F proteins. Some enveloped viruses may exploit such cis interactions with receptors to infect target cells, especially in cell-to-cell transmission. IMPORTANCE Measles virus (MeV) may persist in the brain, causing incurable subacute sclerosing panencephalitis (SSPE). Because neurons, the main target in SSPE, do not express receptors for wild-type (WT) MeV, how MeV propagates in the brain is a key question for the disease. Recent studies have demonstrated that specific substitutions in the MeV fusion (F) protein are critical for neuropathogenicity. Here, we show that weak cis and trans interactions of the MeV attachment protein with receptors that are not sufficient to trigger the WT MeV F protein can trigger the mutant F proteins from neuropathogenic MeV isolates. Our study not only provides an important clue to understand MeV neuropathogenicity but also reveals a novel viral strategy to expand cell tropism.